Increased Left Inferior Temporal Gyrus Was Found in Both Low Function Autism and High Function Autism - Cai, Jia; Hu, Xiao; Guo, Kuifang; Yang, Pingyuan; Situ, Mingjing; Huang, Yi (Frontiers in Psychiatry, 2018)
Most of previous neuroimaging studies have focused on the subjects of Autism Spectrum Disorder(ASD) with IQ >70 or ASD without considering the IQ levels. It remains unclear whether differences in brain anatomy are associated with variations in the clinical phenotype.19 children with low function autism (LFA) and 19 children with high function autism (HFA) were compared with 27 healthy controls(HC). We found increased GMV in left Inferior Temporal Gyrus in both HFA and LFA and increased GMV of Left Middle Temporal Gyrus BA21 was found only in LFA group. Significant negative correlation between LITG and the score of repetitive behavior was found in HFA group.